The Time Course of Repolarization Effects of Intravenous Dofetilide: A Pure Class III Antiarrhythmic Agent - Molnar, Janos; Somberg, John C. (The American journal of cardiology, 2025)
•Dofetilide administered intravenously has a rapid onset of action and the dose of dofetilide is proportional to the prolongation in cardiac repolarization as represented by an increase in QTc interval.•These findings suggest the potential clinical utility of an IV formulation of dofetilide. Dofetilide’s action is inhibition of the potassium channel (IKr) which causes a delay of repolarization as seen on the ECG as QTc prolongation and is its mechanism of antiarrhythmic action. Thus, the time to repolarization prolongation is critical in evaluating the onset of potential antiarrhythmic action. To determine the extent and time course of Dofetilide administered intravenously on cardiac repolarization. Methods: Dofetilide naive healthy subjects 18–45 years received a single dose of 500 mcg dofetilide administered IV over 2.5 hours by constant infusion rate. 12-lead digital Holters recorded the ECG and 20 blood samples were collected. A validated liquid chromatographic method measured dofetilide plasma concentration. The QT intervals were measured by the median beat method from 10‑sec recordings. The Bazett formula was used for QT correction (QTc). Dofetilide concentration continuously increased from the start to the end of the infusion, then gradually decreased. The QTc showed similar dynamics with very early prolongation. At 15 min 50 mcg dofetilide was administered, 1 tenth the recommended dose, with the QTc increasing by 11 ± 10 ms (p = 0.001) indicating early effect on repolarization. There was a strong linear correlation between dofetilide concentrations and QTc intervals (r = 0.95, p < 0.001) with every 1 nanogram increase in plasma concentration resulting in a 17 ms QTc prolongation. The early effect of IV dofetilide on cardiac repolarization suggests dofetilide clinically utility with an immediate antiarrhythmic action. Future clinical studies are indicated to determine optimum dosing, efficacy as well as safety. [Display omitted]